REKAYASA FORMULA PUPUK SUPER ORGANIK DALAM PENERAPANNYA PADA BUDIDAYA TANAMAN SAYURAN BAYAM (Amarantus sp) - Suntoro Suntoro; Slamet Minardi; Sutopo Sutopo (Caraka Tani: Journal of Sustainable Agriculture, 2011)
The decline of soil organic matter in the low of soil productivity. To increase soil of productivity and returns back bearing capacity of the plant, then the business can be done for example by encouraging re-use of organic fertilizers. The study titled “Engineering super organic fertilizer formula in vegetable cultivation on spinach (Amaranthus sp) aims to a). getting a super-organic fertilizer formula, the most good, b). knowing the influence of various super organic fertilizer formula on growth and yield of vegetable Amaranthus sp. The experiment was conducted from April to November 2010. Five kinds of super-organic fertilizer, which is an engineering formula fertilizer that s made from a mixture of manure, sawdust, dolomite, rock phosphate, molasses and starch in the form of granules, making it easier in applying and provide with the same dose. As ground control does not super plus organic fertilizer. Research using Randomized Complete Block Design (RAKL) single factor. The observed variables are observed 1. Independent variables: a. Without organic fertilizer and b. The use of super-organic fertilizer formula 2. Dependent variables include soil chemical properties (properties which are used as a determinant of soil fertility), which consist of: soil pH, soil organic matter content (organic C), cation exchange capacity (KPK), Burnout base (KB), and P is available, and growth spinach plants. The results showed that: super organic fertilizer formula is best P5G2 (mixture of manure, rock phosphate and dolomite with starch adhesive), proved its influence on growth and yield of spinach, either on plant fresh weight, dry weight, root volume and uptake of N gave the highest yield compared with other treatments.